2021
DOI: 10.1590/1806-9282.20210073
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and landscape of Covid-19 vaccines: a review article

Abstract: INTRODUCTION:The rapid advance of Coronavirus disease 2019 has led to the incessant search for therapeutic and prophylactic measures to fight the pandemic. Because it is a viral infection, the safest long-term prophylactic form, in addition to social distance and hygiene, is the vaccine.OBJECTIVE: Thus, this study aimed at conducting a review of the efficacy and landscape of Covid-19 vaccines. METHODS:The following electronic databases were used MEDLINE via PubMed, SCIELO, LILACS, NEJM, and Clinical Trials. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…These various types of vaccines have different safety, efficacy, and production profiles. For example, inactivated vaccines are considered extremely safe, but offer a lower efficacy than vaccines based on viral vectors and nucleic acids [ 4 ]. On the other hand, while viral vectors elicit robust humoral and cell-mediated immune responses against SARS-CoV-2, pre-existing immunity to their viral components is a drawback that may reduce the vaccination’s effectiveness [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These various types of vaccines have different safety, efficacy, and production profiles. For example, inactivated vaccines are considered extremely safe, but offer a lower efficacy than vaccines based on viral vectors and nucleic acids [ 4 ]. On the other hand, while viral vectors elicit robust humoral and cell-mediated immune responses against SARS-CoV-2, pre-existing immunity to their viral components is a drawback that may reduce the vaccination’s effectiveness [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…(11.0%). Based on Garg et al's study results, more comorbid COVID-19 patients were found in the age group 65 years.…”
mentioning
confidence: 94%
“…According to WHO, as of March 2, 2021, there are 76 vaccine candidates in the preclinical trial phase and 182 currently in the clinical trial phase. 11 Several risk factors for COVID-19 are often associated with a poor prognosis, such as advanced age (>65 years), male gender, smoking, and comorbidities. 2,6 Based on the literature review research by Ejaz H et al, the most frequent comorbidities or comorbidities in COVID-19 are hypertension, cardiovascular disease, and diabetes mellitus (DM), followed by obesity, chronic obstructive pulmonary disease (COPD), liver disease, heart disease, and stroke and kidney and malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating correlates of protection for mix-match vaccine against COVID-19 is also meaningful for setting up the benchmark for those countries facing the issue of delivery. Although many vaccines based on different mechanisms to elicit immune response against COVID-19 have been developed [8] , the delivery and the distribution of vaccines in most countries were more challenging than those of high-income countries like Israel where the administration of BNT162b2 (Pfizer-BioNTech) has been swiftly adopted as a nationwide mass vaccination program since December 2020 immediately after the introduction of mRNA vaccine [9] . While it is true that boosting with an mRNA vaccine might increase effectiveness many countries having supply chain issue to administer a homologous second dose are exactly the same countries whether infrastructure is inadequate to maintain the cold chain needed to ensure that the mRNA vaccines remain effective.…”
Section: Introductionmentioning
confidence: 99%